The Other Sister - Zettel, Sarah (New York : Grand Central Publishing, 2018)
Geraldine Monroe is the bad sister. Reckless and troubled, she ran away shortly after the mysterious death of their mother twenty years ago. Marie, on the other hand, has always been the good sister. She is the obedient daughter and a loving mother to her son. Now Geraldine has come home, for good it seems, and no one--not the aunts or uncles or cousins--really knows why. The most suspicious of all is Martin Monroe, the father who rules the extended family and their small town with a poisonous combination of money and coldheartedness. But even he doesnt realize what the truth is: that the sisters have become allies in a plot to kill him. Bound by blood and a need to right the past, Geraldine and Marie set their plan in motion. When old secrets and new fears clash, everyone is pushed to the breaking point . . . and the sisters will learn that they cant trust anyone, not even each other.
Keywords: Kinder- und Hausmr̃chen -- Fiction; Sisters -- Fiction; Fathers and daughters -- Fiction; Family secrets -- Fiction; Revenge -- Fiction; Thrillers (Fiction); Psychological fiction